Caracterização, monitoramento e avaliação de desempenho de pavimentos experimentais com diferentes disposições das camadas de concreto asfáltico - Vieira, Antônio Daniel Boff (2023)
The continuous increase in traffic volume imposes increasingly greater performance demands on the pavement and it is essential that improvements in construction techniques and the use of new materials with better properties occur, such as the use of modified binders to produce asphalt concrete, despite the high cost. In order to alleviate this defect, there are possibilities of using asphalt mixtures with modified binder only in specific parts of the coating layer and continuing to obtain satisfactory results and thus achieving a better cost/benefit ratio. In search of answers about this, three experimental pavements were built, on BR-116 between Pelotas/RS and São Lourenço do Sul/RS, with identical base, sub-base and sub-grade, with differences only in the way the 3 layers are arranged. They are part of the coating, measuring 5 cm each, composed of asphalt concrete with conventional (CAP 50/70) and modified (AMP 50/75-E) binder. These experimental segments were periodically monitored through surveys relating to the percentage of cracked area and rutting. At the same time, the binders and aggregates used in the sections were collected for recomposition and characterization of the mixtures in terms of stiffness, rutting and fatigue of the original mixtures and two versions with change in the modified binder content, upwards and downwards. Computational performance evaluations were performed using MeDiNa and LVECD (FlexPAVETM) software for experimental pavements and other hypothetical scenarios, which showed that the lower layer of the asphalt coating is the most vulnerable to the fatigue phenomenon and, therefore, it is justified the adoption of a better mix, thus making it possible to exemplify some more appropriate strategies for arranging asphalt concrete layers. The laboratory tests indicated that the mixture with conventional binder is less resistant to rutting than the mixture with modified binder and are in accordance with the ATR results found in the field. It can be seen that the use of the mixture, even in the intermediate layer of the coating, provided a drop in performance due to permanent deformation of the pavement. The reduction in the binder content of the mixture with modified binder resulted in an increase in Flow Number, changing it from Class 3 to Class 4, and indicates the possibility of its use in situations of very heavy traffic and severe use, but care is needed since that the fatigue resistance of the mixture was greatly reduced. However, when the binder content of the mixture with modified binder increased, a large reduction in rutting resistance was observed, reaching values comparable to the mixture with conventional binder. In this case, there was only a slight gain in fatigue resistance, but this may become especially relevant when the mixture is used in the lower layer of thick asphalt coatings, as this is the layer most vulnerable to fatigue and at the same time is reasonably protected of high temperatures, being less susceptible to problems with rutting.